Phytotherapeutic potential of Artemisia ludoviciana and Cordia boissieri extracts against the dermatophyte Microsporum canis - Villarreal Villarreal José Pablo; Medina Soto Beatriz A.; Heya Michel Stéphane; Galindo-Rodríguez Sergio A.; Velázquez Uziel Castillo; Cárdenas Noriega Kevin A.; García-Ponce Romario (Journal of Veterinary Research)
Microsporum canis is a dermatophyte that mainly affects dogs and cats. However, it can be transmitted to humans by direct contact. This makes it one of the most frequent causative agents of dermatophytosis in humans, reflecting the frequent human close relationships with pets. Conventional treatment relies on antifungal pharmacological agents. However, errors in application have led to the occurrence of fungal resistance and toxic effects. Consequently, new therapeutic alternatives are needed for M. canis infections. Plant extracts have been explored as phytotherapeutics for the treatment of dermatophyte infections, which prompted an attempt to apply extracts of the ethnopharmacologically important plants Artemisia ludoviciana and Cordia boissieri.